PENERAPAN MEDIA PEMBELAJARAN KAMUS PUTAR DEUTSCH-INDONESISCH DALAM KETERAMPILAN MENULIS KALIMAT DESKRIPTIF BAHASA JERMAN SISWA KELAS X MIA 6 SMAN 2 BANGKALAN - MUSYAROFAH, SITI (LATERNE, 2017)
Writing in a foreign language is most difficult when learning. Students at the SMAN 2 Bangkalan have difficulty finding the idea, especially in descriptive writing. Therefore, teachers as the central components in the learning process must be creative and innovative. In order to help the student, therefore, any learning media that is Kamus Putar Deutsch-Indonesisch applied. Media Kamus Putar selected, because when someone learns German, one always needs a dictionary. The location of the wording book is at first thick and the students are not interested in that. But this media presents a form of the dictionary that is more practical and not equal to the other in general dictionaries. In this essay, researcher take two main things as an object which are : “1) How to apply learning media using Kamus Putar Deutsch-Indonesisch to improve students skills in writing deceptive text. "This research is a true experiment design research using descriptive qualitative research method. This research was conducted at SMAN 2 Bangkalan, while the research sample was class X MIA 6 without applying until applying Kamus Putar Deutsch-Indonesisch media. This study is a descriptive qualitative study. The data sources are obtained through this study to the students in the class X MIA 6 SMAN 2 Bangkalan, which are up to 35 people. Before and after the application of Kamus Putar Deutsch-Indonesisch. The data in this study is the process of applying learning media Kamus Putar Deutsch-Indonesisch, which are done three times. There are also data on the learning results of descriptive writing with learning media Kamus Putar Deutsch-Indonesisch as next data. The results of this study show that the learning medium Kamus Putar Deutsch-Indonesisch is used well and with proper procedures. The result of the observation shows that the students are more active during the learning process. The students like to learn German with the learning medium Kamus Putar Deutsch-Indonesisch, especially in descriptive letters. The ability of the pupils in Germans increases significantly. The learning results of the students are better than before, although there are still some mistakes in writing as in grammar. So the conclusion is drawn that the learning media Kamus Putar German-Indonesian can be used as an alternative to learning German, especially in the teaching of writing. Keywords : Learning Media, Kamus Putar Deutsch-Indonesisch, Descriptive text